Unlocking the full compositional control of hydrophilic and hydrophobic deep eutectic solvents over protein structure and stability - Adrian Sanchez-Fernandez; Jake H. Nicholson; Susana M. Meza Huaman; Claudia Almuzara Romero; Jia-Fei Poon; Sylvain Prevost; Alex P. S. Brogan (Communications Chemistry)
Abstract Deep eutectic solvents (DESs) have emerged as powerful environments to enhance enzymatic reactions, formulate therapeutic proteins, and develop protein-based biomaterials. Despite the wide range of properties that could be achievable through the compositional design of DESs, protein solubilization only happens in a relatively narrow range of hydrophilic DESs. Here, we use surface-modification for the generalized solubilization of proteins in both hydrophilic and hydrophobic DESs. Using surface-modified myoglobin as a model, we show that both DES polarity and hydrogen bond capacity play important roles in dictating the conformational state of the protein. In the hydrophilic DES the protein displays a near-native conformation with an improvement of the thermal stability of + 28 °C compared to aqueous solutions. In contrast, hydrophobic DESs stabilize partially folded intermediates which can refold from temperatures as high as 190 °C. As such, our approach provides a platform to generalize protein incorporation into anhydrous DESs that could be exploited in biocatalysis, biomolecule stabilization, and biomaterials.